2016
DOI: 10.4236/ojog.2016.612089
|View full text |Cite
|
Sign up to set email alerts
|

Concordance in the Interpretation of Cervical Cytology for the Early Diagnosis of Cervical Cancer

Abstract: Objective: To identify the diagnostic concordance in the interpretation of cervical smears. Material and Methods: Cross-sectional study from October 2011 to January 2013. 50 samples were read by every 4 cyto-technologists who are the total staffs that read and interpret cytological specimens from a public health institution of the city of San Luis Potosí, México. The cytological diagnosis was confirmed by a certified pathologist. Checklist was developed to determine the quality of the interpretation composed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 7 publications
(6 reference statements)
0
7
0
Order By: Relevance
“…To decrease these rates for CLM and for WSI by CT and pathologists, more practical training and education are needed. [ 20 30 31 32 33 ] Overall and compared to the published literature on the subject, 2 cohorts of approximately 500 cases each which were enriched for high-grade cases comprise the largest study group used in digital cytology so far. The results of our study allow to give directions for further steps to prepare the introduction of digital cytology as a routine diagnostic technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To decrease these rates for CLM and for WSI by CT and pathologists, more practical training and education are needed. [ 20 30 31 32 33 ] Overall and compared to the published literature on the subject, 2 cohorts of approximately 500 cases each which were enriched for high-grade cases comprise the largest study group used in digital cytology so far. The results of our study allow to give directions for further steps to prepare the introduction of digital cytology as a routine diagnostic technique.…”
Section: Discussionmentioning
confidence: 99%
“…At the time of this writing, there were few published studies investigating the use of WSI in primary cytology diagnostics. [ 8 10 18 19 20 21 22 23 30 31 ] Steinberg and Ali achieved an accuracy of 98.3% comparing WSI with CLM examination by six participants of ten selected thin-layer cervical slides. [ 19 ] A next study investigated the accuracy of 24 experienced cytologists in the examination of WSI from 24 cervical thin-layer slides which appeared to be equal to glass slide microscopy when participants were able to focus through the full thickness of the slide.…”
Section: Discussionmentioning
confidence: 99%
“…It should be mentioned that, in the present study, the professionals who analyzed the biopsies (double blind) were certified pathologists; however, staff training should be considered 5 since, in some studies, such as the study conducted by Gutíerrez-Enríquez, 6 differences in cytological diagnosis between cytotechnologists and pathologists were evident. They found that, in their evaluations of epithelial abnormalities, only one of the cytotechnologists had significant concordance with the pathologists; however, the concordance was low.…”
Section: Discussionmentioning
confidence: 93%
“…The authors concluded that the concordance between cytotechnologists and pathologists is below the required minimum level set by national and international standards. 6…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation